Developing professionalism in engineering students using problem based learning - Jianguo, Wang; Yew, Chan Fong; W. A. M., Alwis (2005)
This paper discusses the professionalism of engineering and its meaning to engineering education. Through evaluating the traditional ways of engineering education in universities and institutes of high learning, the paper shows the need for an engineering education strategy that enable students to evaluate a given scenario, identify, search & gather relevant information, work in teams, reason & justify to form opinions, apply various known tools, convince others and reflect regularly on whatever they do. The paper introduces problem based learning (PBL) approach for professional development in engineering education. It elaborates on the design and implementation of RP-PBL (Republic Polytechnic –PBL) approach within the School of Engineering, Republic Polytechnic, Singapore. As a part of the curriculum, collaboration with the industry and engineering professional bodies like Institution of Engineers Singapore (IES) and Singapore Industrial Automation Association (SIAA) to nurture the professionalism of engineering students is also discussed.